Science to Practice: Enhancing Photothermal Ablation of Colorectal Liver Metastases with Targeted Hybrid Nanoparticles - Yang, Xiaoming (Radiology, 2017)
Image-guided percutaneous thermal ablation has been one of the principal tools in management of unresectable liver malignancies, including colorectal liver metastases (CRLM) (1). Currently, however, this technique is suitable mainly for tumors less than 4–5 cm in diameter and also results in incomplete ablation at tumor margins (2). To solve these problems, efforts have been made to combine thermal ablation with other treatment options, such as systemic and intra-arterial administration of therapeutics (3–5). In this issue of Radiology, White et al (6) introduced their work on development of an alternative approach by using biofunctionalized hybrid magnetic gold nanoparticles (HNPs) as catalysts for photothermal ablation of CRLM. They found that (a) the targeted (anti-MG1) HNPs are noncytotoxic and have greater than 20% intratumoral accumulation and (b) systemic administration of anti-MG1 HNPs can enlarge a tumor’s necrotic zone with photothermal ablation. The results of this study establish the proof of the concept that targeted HNPs can enhance the therapeutic effect of photothermal ablation, which presents an exciting strategy for complete removal of CRLM by integrating two rapidly advancing scientific fields—interventional radiology and nanotechnology.